Floristic and functional affiliations of woody plants with climate in western Amazonia - Butt, N; Malhi, Y; Phillips, O; New, M (Blackwell Publishing, 2008)
Aim: To test whether a direct relationship exists between the relative abundance of woody plant genera and precipitation regime along the north-south climate gradient of the western Amazonia. Location: Lowland rain forests in the western Amazon. Methods: Floristic data on 91 woody plant genera, from 39 0.1-ha plots across the western Amazon, and precipitation data from a 0.5° global data set were used to test for correlations between plant relative abundance (defined as percentage number of stems ≥ 2.5 cm diameter at breast height for each woody plant genus per plot) and derived dry-season variables. Moisture preference was then assessed in terms of pioneer and shade-tolerant life-history strategy. Results: There were significant associations between the distribution of plant relative abundances and seasonal precipitation variables in 34% of genera analysed. Significant differences were identified in size-class distribution between dry affiliates and generalists. Dry affiliates were not dominant in any size class in any plot type, whereas climate generalists dominated most of the size classes in the dry plots and the mid-range size classes in the wet plots. Dry-affiliate genera were a minority, even in dry forests. Wet-affiliate genera were correlated with shade tolerance, whereas genera with no rainfall affiliation were often pioneers. Main conclusions: The results suggest that moisture variable seasonality influences community composition in a manner than can be related to the life-history trade-off between shade tolerance and pioneer ranking. One possible reason for higher diversity in wetter forests is that high rainfall amplifies the niche space available to shade-tolerant plants. Determining which plant groups are constrained by which environmental variables can contribute to our understanding of how forest composition may be changing now, and how it may change under future climate: if shade-tolerant trees are also drought-intolerant, community structure in wet forests may be more vulnerable to future increases in moisture stress.